Bandas de predição usando densidade condicional estimada e um modelo LDA com covariáveis - Shimizu, Gilson Yuuji (2021)
Machine learning methods are divided into two main groups: supervised and unsupervised methods. In the first part of this work, we develop a method for creating prediction bands that can be applied to supervised problems. Our approach is based on conformal methods, which are very appealing because they create prediction bands that control average coverage assuming solely i.i.d. data. It is also often desirable to control conditional coverage, that is, coverage for every new testing point. However, without strong assumptions, conditional coverage is unachievable. Given this limitation, the literature has focused on methods with asymptotical conditional coverage. In order to obtain this property, these methods require strong conditions on the dependence between the target variable and the features. We introduce two conformal methods based on conditional density estimators that do not depend on this type of assumption to obtain asymptotic conditional coverage: Dist-split and CD-split. While Dist-split asymptotically obtains optimal intervals, which are easier to interpret than general regions, CD-split obtains optimal size regions, which are smaller than intervals. CD-split also obtains local coverage by creating prediction bands locally on a partition of the features space. This partition is data-driven and scales to high-dimensional settings. In a wide variety of simulated scenarios, our methods have a better control of conditional coverage and have smaller length than previously proposed methods. In the second part, in a context of unsupervised methods, we develop a new version of the Latent Dirichlet Allocation (LDA) model. The LDA model is a popular method for creating mixed-membership clusters. Despite having been originally developed for text analysis, LDA has been used for a wide range of other applications. We propose a new formulation for the LDA model which incorporates covariates. In this model, a negative binomial regression is embedded within LDA, enabling straight-forward interpretation of the regression coefficients and the analysis of the quantity of cluster-specific elements in each sampling units (instead of the analysis being focused on modeling the proportion of each cluster, as in Structural Topic Models). We use slice sampling within a Gibbs sampling algorithm to estimate model parameters. We rely on simulations to show how our algorithm is able to successfully retrieve the true parameter values. The model is illustrated using real data sets from three different areas: text-mining of Coronavirus articles, analysis of grocery shopping baskets, and ecology of tree species on Barro Colorado Island (Panama). This model allows the identification of mixed-membership clusters in discrete data and provides inference on the relationship between covariates and the abundance of these clusters.